The Influence of Hot Point on MTU CB Condition at the Pgeli-Giugur 1 Bay Line (PT. PLN Paya Geli Substation) - Dina Maizana; Cando Situmorang; Habib Satria; Yanawati Binti Yahya; Muhammad Ayyoub; Manoj V. Bhalerao; Ashif Mohammad (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
Local heating that occurs in substation equipment is caused by the current flowing in the conductor due to resistance. The parts that often experience heating are the terminals and connections at the substation, especially between two different metals, as well as the conductor cross-section which decreases due to corrosion. So that part must be considered. As for how to control or check the temperature is done by using thermovision. The heat temperature of the Circuit Breaker (CB) equipment at the Bay line PGELI-GIUGUR1 at Paya GeIi Substation is still in normal conditions where the temperature ranges from 20oC-43oC. But one phase need attention if temperature more than 70oC, it is needed for improvement plans. The temperature difference between the phases of the CB equipment at Bay Iine P. GELI-GLUGUR 1 at Paya Geli Substation has reached condition 5 (five), so it needs serious attention and a repair plan, to avoid short circuits between phases (R, S, T).